STRATEGI KEPOLISIAN DALAM MENCEGAH PROSTITUSI ANAK (Studi Pada Polresta Pekanbaru) - Stefan Abidin, Dendi; Usmita , Fakhri (SISI LAIN REALITA, 2022)
The child is someone who is not yet eighteen years old and in carrying out his life, the child must be fulfilled every right he has and get attention and protection in the process of growth and development. However, in several big cities in Indonesia, not all children can grow and develop properly including children experiencing intimidation, violence, exploitation, as happened in Pekanbaru city where there is prostitution involving children, this research was conducted in Pekanbaru city which focused on the jurisdiction Polresta Pekanbaru and included in the type of descriptive qualitative research where based on interviews resulted in data findings that there are police efforts and strategies in preventing child prostitution. Then an analysis is carried out using the theory of crime prevention, namely pre-emptive which includes prevention by instilling values ​​and norms into the community as a form of early prevention, preventive by preventing crime before the occurrence of a crime by suppressing the opportunity to commit a crime, repressive is an effort made when the crime occurs. happened and the police enforce the law.